2014
DOI: 10.1111/bph.12631
|View full text |Cite
|
Sign up to set email alerts
|

Acute desipramine restores presynaptic cortical defects in murine experimental autoimmune encephalomyelitis by suppressing central CCL5 overproduction

Abstract: BACKGROUND AND PURPOSEAltered glutamate exocytosis and cAMP production in cortical terminals of experimental autoimmune encephalomyelitis (EAE) mice occur at the early stage of disease (13 days post-immunization, d.p.i.). Neuronal defects were paralleled by overexpression of the central chemokine CCL5 (also known as RANTES), suggesting it has a role in presynaptic impairments. We propose that drugs able to restore CCL5 content to physiological levels could also restore presynaptic defects. Because of its effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 49 publications
5
32
0
Order By: Relevance
“…These symptoms are rarely assessed in rodent models, despite their frequent association with MS. Assessment of nociceptive hypersensitivity in relapsing remitting models is limited, but several studies have demonstrated pharmacological reversal of allodynia (Khan et al, 2014; Lu et al, 2012; Lynch et al, 2008; Ramos et al, 2010; Schmitz et al, 2014; Sloane et al, 2009; Thibault et al, 2011; Tian et al, 2013). While anxiety behaviors are a known feature in EAE models (Acharjee et al, 2013; Peruga et al, 2011; Pollak et al, 2000), only two studies have evaluated therapeutic modulation (Di Prisco et al, 2014; Haji et al, 2012). Our study is the first to quantify such a breadth of EAE-associated behaviors, and further introduces a measure of fatigue, as well as demonstrating reversal with XT-101-R.…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms are rarely assessed in rodent models, despite their frequent association with MS. Assessment of nociceptive hypersensitivity in relapsing remitting models is limited, but several studies have demonstrated pharmacological reversal of allodynia (Khan et al, 2014; Lu et al, 2012; Lynch et al, 2008; Ramos et al, 2010; Schmitz et al, 2014; Sloane et al, 2009; Thibault et al, 2011; Tian et al, 2013). While anxiety behaviors are a known feature in EAE models (Acharjee et al, 2013; Peruga et al, 2011; Pollak et al, 2000), only two studies have evaluated therapeutic modulation (Di Prisco et al, 2014; Haji et al, 2012). Our study is the first to quantify such a breadth of EAE-associated behaviors, and further introduces a measure of fatigue, as well as demonstrating reversal with XT-101-R.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is intriguing when considering that, in EAE mice at the early stage of disease, cyclic adenosine monophosphate production was drastically reduced in cortical nerve endings and forskolin could no more release glutamate (Di Prisco et al, ), suggesting that in these mice CCR oligomers do not couple efficiently to adenylyl cyclase (AC). Interestingly, the loss of function of AC was strictly related to CCL5 overexpression, since pharmacological interventions restoring CCL5 amount to physiological level also recovered AC activity and its negative coupling to CCR oligomers (Di Prisco et al, ). These observations led us to propose that the loss of function of AC in cortical glutamatergic nerve terminals might have favored the unusual coupling of CCRs to a dissimilar enzymatic pathway, giving the rationale for the switch from inhibition to facilitation of the presynaptic CCL5‐mediated control of glutamate exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Female mice (C57BL/6; 18–20 g, 6–8 weeks) were immunized with myelin oligodendrocyte glycoprotein (MOG) 35–55 according to a standard protocol previously described (Di Prisco et al, ). Briefly, animals were subcutaneously injected with incomplete Freund's adjuvant containing 4 mg/ml Mycobacterium tuberculosis (strain H37Ra) and 200 µg of the MOG 35–55 peptide.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations